Clinical, dermoscopic, reflectance confocal microscopic and histopathological features of atypical scabies: an analysis of 60 cases - Peng WANG; Jianyong LIU; Xinmei LIU; Shirong YU; Dezhi ZHANG; Xiaojing KANG (Pifu-xingbing zhenliaoxue zazhi, 2023)
Objective To analyze the dermoscopic, reflectance confocal microscopic and histopathological features of 60 cases of atypical scabies. Methods Sixty cases of atypical scabies were analyzed in terms of demographic data, disease duration, and clinical, dermoscopic and reflectance confocal microscopic features. Skin histopathology was performed in 25 patients. Results A larger portion of the patients were aged 18-65 years (40.00%). Retirees, students and migrant workers accounted for 36.67% (22 cases), 20.00% (12 cases) and 18.33% (11 cases), respectively. The average disease duration was 38.12±22.56 days. Twenty-seven patients (45.00%) had a history of contact with patients with scabies. The commonly involved body sites were the palms (52 cases, 86.67%), abdomen (49 cases, 81.67%), wrists (44 cases, 73.33%) and vulva (38 cases, 63.33%). The most common skin rashes were papules (55 cases, 91.67%). Most patients had been misdiagnosed more than twice. The misdiagnoses included pruritus (17 cases, 28.33%), atopic dermatitis (16 cases, 26.67%) and eczema (14 cases, 23.33%). Over 60% of the misdiagnosed patients were treated with glucocorticoids (38 cases, 63.33%). Dermoscopic features included white burrows with triangular structures in brown or dark brown color at the end of burrows (48 cases) and gray-edge lines (42 cases). The typical mite body, burrows and feces were observed in 55 cases under a reflectance confocal microscope. Histopathologically, mites or eggs were seen in the stratum corneum in 17 out of 25 cases, and acute or subacute dermatitis with spongy edema were observed in 12 cases. Dermal infiltrates of eosinophils and lymphocytes were seen in 18 and 7 cases, respectively. Conclusions Atypical scabies displays divergent clinical features. Dermoscopy, reflectance confocal microscopy and histopathology are helpful in the diagnosis of atypical scabies.